ESTIMATION OF THE NUMBER OF EDUCATIONAL SUPPORT OF PERSONNEL LABORATORIES OF STATISTICS DEPARTMENTS - Harbaruk, V. V.; Herasymenko, P. V.; Elyzarov, S. V.; Khodakovskyi, V. O. (Science and Transport Progress, 2005)
The article provides methodical guideline on construction of mathematical model for evaluation of the number of auxiliary educational staff for provision of training workshops of all kinds.